Identification of Dominant Microbial Community and Diversity in Continuously Cropped Pepper Fields - Wang, Hui; Liu, Li; Yu, Shuyi; Guan, Tianshu; Li, Baihong; Wang, Qi; Liu, Changyuan (Weon'ye gwahag gi'sulji, 2021)
Pepper blight is the most significant soil-borne disease affecting the continuous cropping ofpeppers. To identify the effect of Phytophthora capsici infection on microbial flora, we isolated andcounted the microorganisms collected from the rhizosphere soil of P. capsici-affected farms thatcontinuously cropped pepper for 3, 6, and 9 years in Liaoning Province, China. The colony and cellmorphology, physiological and biochemical characteristics, and 16S rDNA sequence of bacteriaand actinomycetes were documented. In addition, colony and microscopic morphology of fungi andthe rDNA-ITS sequence were analysed for classification. We observed that healthy and diseasedpeppers had the largest number of bacteria in the rhizosphere followed by actinomycetes and fungi. After infection, the number of bacteria and actinomycetes decreased with a corresponding increasein the number of fungi, leading to a reduction in the ratio of bacteria/fungi to actinomycetes/fungi. We identified 15 dominant bacterial strains, of which Bacillus represented the most abundant genusconsisting of 7 strains followed by Flavobacterium and Staphylococcus. Furthermore, 15 of the 17actinomycetes strains belonged to the genus Streptomyces. Among the six fungal strains, we foundP. infestans, Fusarium, and Penicillium consisting of two strains each. This study elucidated theimpact of pathogenic P. capsici on the composition of soil microbes over time and characterizedseveral cultivatable dominant bacterial groups, which can provide a basis for practical interventionstrategies to improve soil conditions for continuous cropping. KCI Citation Count: 0